Распределение напряжений на вытяжном ребре матрицы привытяжке цилиндрических заготовок - Аргат, Роман Григорьевич; Пузырь, Руслан Григорьевич; Долгих, Ольга Николаевна (НТУ "ХПИ", 2014)
В статье приведены результаты теоретического анализа процесса вытяжки цилиндрических деталей из листового металла, учитывающие влияние технологических и геометрических параметров процесса на распределение опасных растягивающих напряжений на вытяжном ребре матрицы. Рассмотрено равновесие тороидальной оболочки без учета влияния касательных напряжений. Получена зависимость для расчета величины растягивающих напряжений на вытяжной кромке матрицы,которая позволяет учитывать влияние коэффициента вытяжки,угла охвата вытяжной кромки матрицы материалом заготовки,толщины последней и радиуса закругления матрицы.

In the article the theoretical analysis of process of extraction of cylindrical details is conducted from a sheet-metal. It is shown that extraction is the widespread enough and productive method of receipt of cylindrical details from a sheet. However, in a theoretical plan influence of technological and geometrical parameters of process is full not enough exposed on distribution of dangerous stretchings tensions on the drawing rib of matrix. The equilibrium of toroidal shell was examined, from equalizations of equilibrium members, containing tangent tensions in connection with axial symmetry of deformation, were eliminated. As a result of decision jointly with the condition of plasticity dependence is got for the calculation of size of stretchings meridian tensions on the drawing edge of matrix, which allows to take into account influence of coefficient of extraction, corner of scope of drawing edge of matrix by material of purveyance, thickness of the last and radius of rounding of matrix, that enables to take into account influence of aggregate of factors on the sizes of tension P.
Distribution of tensions on the drawing rib of matrix at extraction of cylindrical purveyances
Keywords: цилиндрические заготовки; вытяжка; деформация; листовая штамповка; листовые звготовки; extraction